Computer organization and design: The hardware/software interface - Patterson, David A.; Hennessy, John L. (New Delhi Relx India Pvt. Ltd., 2024)
Key Features covers parallelism in-depth, with examples and content highlighting parallel hardware and software topics includes new sections in each Chapter on domain specific architectures (DSA) discusses and highlights the "eight great ideas" Of computer architecture, including performance via parallelism, performance via pipelining, performance via prediction, design for moore's law, hierarchy of memories, abstraction to simplify design, make the common case fast and dependability via redundancy.